(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
The prediction of surface temperature induced by frictional heating is of significance for evaluating the serious thermal wear, erosion and lubrication failure for industrial application and design. Temperature prediction model was established with two steps. Local temperature was calculated firstly with the real contact area based on the fractal analysis. Then, the finite element prediction model were established with the above value of local temperature, on the basis of wavelet finite element. Finally, the whole temperature of the fractal engineering surface were demonstrated and simulation results were shown. Moreover, orthogonal simulations were conducted to study the influence of the input parameters of fractal dimension, fractal characteristic length and material thermal properties. Results with different cases demonstrated that all the temperature decreased gradually from the contact surface to the bottom and the temperature increased with the rise of heat transfer properties, fractal dimension and fractal characteristic length for the same position. However, heat transfer properties had the most obvious influence on the temperature rise, and the following one was fractal dimension.